Prevalence of Workaholism Among Egyptian Healthcare Workers With Assessment of Its Relation to Quality of Life, Mental Health and Burnout - Kasemy, Zeinab A.; Abd-Ellatif, Eman E.; Abdel Latif, Asmaa A.; Bahgat, Nadia M.; Shereda, Hanaa Mohammad Abo; Shattla, Safaa Ibrahim; Aboalizm, Samira E.; Abd Elhy, Asmaa Hamed; Allam, Abeer R.; Ramadan, Ahmed N.; Amer, Hemat Mostafa; Ahmed, Naglaa Abdelmawgoud; et al. (Frontiers in Public Health, 2020)
Introduction: Work is a social double edged weapon activity that may have positive and negative effects on individual's quality of life and health. Objectives: To estimate workaholism prevalence and to determine its effects on quality of life, mental health, and burnout among healthcare workers (HCWs). Methods: Using a cross-sectional study, 1,080 Egyptian participants distributed as HCWs and non-HCWs were recruited. The study included 4 questionnaires to assess workaholism, quality of life (QoL), Psychological capital questionnaire (PCQ), and General health questionnaire (GHQ). Maslach Burnout Inventory (MBI) was applied to critical specialty HCWs in addition to pro-inflammatory markers including Il6, TNFα, and CoQ10. Results: This study revealed that 24.4 and 24.8% of HCWs were workaholic and hardworking, respectively, in comparison to 5.9 and 28.1% among non-HCWs (P < 0.001). Somatic symptoms and anxiety/ insomnia domains of GHQ were higher among HCWs than non-HCWs (P < 0.001 and 0.002, respectively). QoL was significantly lower among HCWs than non-HCWs (P < 0.001). Workaholism was reported among 43.2% of HCWs with critical specialty (P < 0.001). Components of PCQ components were significantly higher among HCWs with critical specialty than non-critical HCWs while QoL showed the reverse (P < 0.05). Working excessively was a predictor to burnout [Emotional exhaustion (β = –0.23) and depersonalization (β = −0.25)] and TNFα (β = 0.41). Emotional exhaustion was a predictor to Il6 (β = 0.66), TNFα (β = 0.73), and CoQ10 (β = −0.78). Conclusion: There is a significant association between workaholism and psychologically poor-health and poor quality of life among HCWs. Critical specialty healthcare workers showed association between workaholism, burnout and pro-inflammatory markers. Addressing of personal characteristics, supporting factors in the work environment and periodic examination of the healthcare workers and responding accordingly is required.